Frequency and Type of Hepatic and Gastrointestinal Involvement in Juvenile Systemic Lupus Erythematosus. (29th November 2017) - Tahernia, Leila; Alimadadi, Hosein; Tahghighi, Fatemeh; Amini, Zahra; Ziaee, Vahid
Abstract : Background. Systemic lupus erythematosus (SLE) is a frequent rheumatology disorder among children. Since hepatic involvement is a common systemic manifestation in lupus, the frequency and type of hepatic involvement were determined in pediatric cases of SLE admitted to Children's Medical Hospital from 2005 to 2014. Methods and Patients. In this observational case-series study, 138 pediatric cases of SLE were admitted in Children's Medical Center (a pediatric rheumatology referral center in Tehran, Iran) enrolled from 2005 to 2014 and the outcomes, frequency, and type of hepatic involvement were assessed among them. Results. Hepatic involvement was reported in 48.55% of total SLE patients. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), and both enzymes higher than normal upper limits were detected in 8.7%, 5%, and 34.7% of lupus patients, respectively. Increased level of liver enzymes was categorized as less than 100, between 100 and 1000, and more than 1000 levels in 23.1%, 23.1%, and 2.1% of cases. The only gastrointestinal involvement in lupus patients contributing to hepatic involvement was gastrointestinal bleeding. Rising in liver enzymes was detected mostly in lupus patients without gastrointestinal bleeding (52.2% without versus 25.8% with gastrointestinal bleeding, P = 0.007 ). Conclusion. Approximately half of the pediatric patients suffering from SLE have hepatic involvement. No significant correlation was observed between various organs involvement and abnormal level of liver enzymes.